2012
DOI: 10.2337/db12-0072
|View full text |Cite
|
Sign up to set email alerts
|

GSH or Palmitate Preserves Mitochondrial Energetic/Redox Balance, Preventing Mechanical Dysfunction in Metabolically Challenged Myocytes/Hearts From Type 2 Diabetic Mice

Abstract: In type 2 diabetes, hyperglycemia and increased sympathetic drive may alter mitochondria energetic/redox properties, decreasing the organelle’s functionality. These perturbations may prompt or sustain basal low-cardiac performance and limited exercise capacity. Yet the precise steps involved in this mitochondrial failure remain elusive. Here, we have identified dysfunctional mitochondrial respiration with substrates of complex I, II, and IV and lowered thioredoxin-2/glutathione (GSH) pools as the main processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
160
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(173 citation statements)
references
References 47 publications
13
160
0
Order By: Relevance
“…4, A and B), and restoration of cellular/ mitochondrial cardiac redox balance in HG may play a causal rather than correlative role for preserving contractility (Fig. 5) (51). Together, these data suggest that GSH regeneration and ROS scavenging underlie enhanced contractility in T2DM.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…4, A and B), and restoration of cellular/ mitochondrial cardiac redox balance in HG may play a causal rather than correlative role for preserving contractility (Fig. 5) (51). Together, these data suggest that GSH regeneration and ROS scavenging underlie enhanced contractility in T2DM.…”
Section: Discussionmentioning
confidence: 66%
“…Under loaded conditions the muscle is stretched to reach the optimal sarcomere length, thus different from unloaded Langendorff-perfused hearts (54). Also the detrimental effects of hyperglycemia were evident only in the presence of the higher energetic demand imposed by ␤-adrenergic stimulation in diabetic mice (51).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studying the selectivity of these lipases has applications in understanding diseases, including fat malabsorption disorders, hypercholesterolemia, atherosclerosis, and diabetes (9,10). Research on metabolic disorders has shown that fatty acid accumulation can exert a toxic or a protective effect on a tissue, depending on the specific tissue type (e.g., liver, cardiac, or skeletal muscle) (11,12) and health state (e.g., diabetic) (13,14) as well as on the fatty acids (e.g., saturated or unsaturated) (15). Sequestration of fatty acids by esterification to glycerides is one pathway by which these effects are regulated (16).…”
mentioning
confidence: 99%